Need Assessment for Digital Skills Development of School Administrations - Sanchai, Jenjira; Koomkhainam, Tanongsak (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: Digital skills are an important skill in today's era, especially for school administrators who are the leaders of the organization Digital knowledge and skills are required. To be able to manage educational institutions to achieve their goals efficiently and productively. The purposes of this research were to 1) study the current of digital skills of school administrators, 2) study the desirable digital skills of school administrators, and 3) study the necessary conditions of digital skills of school administrators under the Buengkan Secondary Educational Service Area Office. Methodology: The sample was 16 school administrators and 262 teachers, 278 samples in total, using stratified random sampling divided by school size, and then performed simple random sampling. The research instrument was a questionnaire of which the content validity was in the range of 0.67 – 1.00 and reliability was at 0.991. Percentage, mean, and standard deviation were used for data analysis, PNImodified formula was used to sort the current, desirable, and necessary conditions. Results: 1) The overview of the study of the current condition of digital skills of school administrators is at a high level. 2) The desirable condition of digital skills of school administrators was, on average, at the highest level. 3) The highest necessary condition was the digital applying skill for the development and enhancement of the potential of the organization, followed by using digital to manage and lead the organization skill, digital law compliance skills, respectively, and knowledge and use of digital technology skills. Conclusion: The digital skills of all school administrators are at a high level and the needs index shows the importance of digital applications in organizational development, management, compliance with digital laws and Know and use digital technology.